Understanding Egyptians’ Green Consumerism: An Exploratory Investigation - AL-Sahouly, Ibrahim (Archives of Business Research, 2020)
This study contributes to the literature of Egyptian green consumerism as minimum empirical investigations that relate to this scope of research have been conducted in Egypt, especially with the younger consumers. The objective of this research is to investigate young Egyptian consumers’ purchasing intention towards plastic recycled products for the purpose of providing guidelines to Egyptian companies pursuing eco consumers. Based on the outcomes of the empirical investigation, survey results showed that there is a relationship between price, labelling and intention to purchase recycled products, while no relation was found between awareness and intention to purchase. The paper proposes valuable recommendations for Egyptian marketers to adopt green strategies.